Nutritional anti-nutritional chemical composition and antioxidant activities of the leaves of the sea cliff dwelling species Limonium spathulatum (Desf.) Kuntze - Youssef, Seria; Custódio, Luísa; Rodrigues, Maria João; Pereira, Catarina G.; Calhelha, Ricardo C.; Pinela, José; Barros, Lillian; Jekő, József; Cziáky, Zoltán; Ben Hamed, Karim (Frontiers in Plant Science, 2022)
This work explored for the first time the nutritional and anti- nutritional properties of leaves of the halophytic species Limonium spathulatum (Desf.) Kuntze from Tunisian sea cliffs. The in vitro and ex vivo antioxidant properties and the total levels of phenolics and tannins of food grade extracts prepared from its leaves are also reported. L. spathulatum leaves had high levels of moisture, ash, NDF, and ADF , but low concentrations of crude protein, crude fat and ADL. They contained low carbohydrates levels, and low energetic values. The most abundant macroelements were Cl-, Na and Ca while the microelements detected in the highest levels were Fe and Zn. The toxic elements Pb and Cd were not detected. A high trypsin inhibition was observed in the water extract, followed by the hydroethanolic and ethanol extracts. No relevant -amylase inhibition was observed, and no phytic acid was detected. Taken together, these results suggested that L. spathulatum leaves can be considered as source of nutrients for human consumption. The TPC peaked in the waterand hydroethanolic extracts, followed by the ethanol extract. In the contrary, the ethanol extract had the highest level of flavonoids, followed by the hydroethanolic and the water extracts. The ex vivo antioxidant properties by oxidative haemolysis inhibition (OxHLIA) and lipid peroxidation inhibition by thiobarbituric acid reactive substances (TBARS) formation. The hydroethanolic and the ethanol extracts displayed the highest capacity to inhibit lipid peroxidation. The same samples were also the most active towards oxidative haemolysis. The extracts from the leaves of L. spathulatum, high in polyphenols and/or flavonoids, showed in vitro and ex vivo antioxidant activities, make of this species a source of innovative bioactive natural products.